2017
DOI: 10.5336/gynobstet.2016-54030
|View full text |Cite
|
Sign up to set email alerts
|

Is it Logical Excising All of the Postmenopausal Polyps?

Abstract: n cases of endometrium cancer one out of 5 patient were asymptomatic at the time of diagnosis. Consequently, asymptomatic cases, especially at the menopausal period, examined detailed in order not to misdiagnose a cancer case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…31 The other important reason for this combination was the inconsistency in reporting amongst the included studies which would have made pooling impossible. Six studies documented separate analysis for non-atypical, atypical hyperplasia and cancer, 46,2527 two studies classified non-atypical hyperplasia as a normal finding, 15,30 one study combined all hyperplasias together, 29 and one study reported only cancer cases. 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The other important reason for this combination was the inconsistency in reporting amongst the included studies which would have made pooling impossible. Six studies documented separate analysis for non-atypical, atypical hyperplasia and cancer, 46,2527 two studies classified non-atypical hyperplasia as a normal finding, 15,30 one study combined all hyperplasias together, 29 and one study reported only cancer cases. 28…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies were excluded because of lack of reporting separate results for women with PMB, which might have affected the estimated prevalence in this review. A potential source of heterogeneity and bias in the study is that three studies 25,28,30 had not documented the definition of the menopause used in their reports, and another study 6 defined the menopause as cessation of menstruation for ≥6 months (rather than 12 months) after the age of 45 years. It is impossible to know whether this had led to including some perimenopausal women in the analysis.…”
Section: Discussionmentioning
confidence: 99%